Effects of visual expertise on a novel eye-size illusion: Implications for holistic face processing. (August 2015) - Fu, Genyue; Dong, Yan; Quinn, Paul C.; Xiao, Wen S.; Wang, Qiandong; Chen, Guowei; Pascalis, Olivier; Lee, Kang
Highlights: The eye-size illusion was more pronounced with own-race than with other-race faces. The eye-size illusion was more pronounced with own-age than with other-age faces. Visual experience with faces influences the magnitude of the eye-size illusion. Holistic processing may play a role in engendering the eye-size illusion. Abstract: We examined the effect of visual experience on the magnitude of a novel eye-size illusion: when the size of a face's frame is increased or decreased but eye size is unchanged, observers judge the size of the eyes to be different from that in the original face frame. In the current study, we asked Chinese and Caucasian participants to judge eye size in different pairs of faces and measured the magnitude of the illusion when the faces were own- or other-age (adult vs. infant faces) and when the faces were own- or other-race (Chinese vs. Caucasian faces). We found an other-age effect and an other-race effect with the eye-size illusion: The illusion was more pronounced with own-race and own-age faces than with other-race and other-age faces. These findings taken together suggest that visual experience with faces influences the magnitude of this novel illusion. Extensive experience with certain face categories strengthens the illusion in the context of these categories, but lack of it reduces the magnitude of the illusion. Our results further imply that holistic processing may play an important role in engendering the eye-size illusion.